“What We Want is the Same Thing You Want”: Educator Union Organizing for the ‘Common Good’ during Covid-19 - Maton, Rhiannon M. (Radical Teacher, 2022)
This article examines the “common good” organizing efforts of U.S. educator unions during the 2020-2021 school year of the Covid-19 pandemic. During this timeframe, many districts across the country pushed for school reopening while often appearing to pay insufficient attention to the lived health and safety needs of students, families, and workers in schools and their broader communities. Meanwhile, many U.S. educator unions assertively and visibly organized for a “safe return to school” involving stronger health protections in public school buildings. Embracing social justice unionism as an organizing philosophy, such unions employed a range of tactics in efforts to partner with local communities while advocating for common good issues that would benefit not just their members but also the public more broadly. Drawing upon a range of popular media and artifactual union-published sources combined with educator unionist interviews, this article teases apart what common good issues were taken up by social justice unions in their organizing efforts, discusses why they chose to take up this range of issues, and considers the stakes of this frame for union organizing within and beyond the Covid-19 pandemic.